Réponses

2014-05-19T19:28:36+02:00
A = 4xaxa - axy + ax1
=ax(4ax-4y+1)

B = 3 (2x+1) - (2x+1) (2x+1)
=(2x+1)[3-(2x+1)]
=(2x+1)(3-2x-1)
=(2x+1)(-2x-2)
=-2(2x+1)(x+1)

C = (3x-7) (-5x+1) - (-5x +1) (4-2x)
=(-5x +1)[3x-7-(4-2x)]
=(-5x +1)(3x-7-4+2x)
=(-5x +1)(5x-11)
  • Utilisateur Brainly
2014-05-19T19:56:41+02:00
Bonjour, 

A = 4*a*a - a*y + a*1
A= a(4a - y + 1)

B = 3 (2x+1) - (2x+1) (2x+1)
B= (2x + 1)(3 - 2x - 1)
B= (2x + 1)(- 2x + 2)

C = (3x-7) (-5x+1) - (-5x +1) (4-2x)
C= (- 5x + 1)(3x - 7 - 4 + 2x)
C= (- 5x + 1)(5x - 11)